The Analysis Of Bima And English Language Pronouns - Waliyudin, Waliyudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The focus of this study was attempt to describe and contrast the aspect and the use of pronouns. The design of this study belongs to qualitative descriptive study. It refers to the following criteria: (1) having one natural setting as the data sources, (2) using the researcher as the key instrument, (3) having much concern with the process rather than the outcomes, (4) being descriptive in nature, (5) having much concern with the utterances or words as the analysis of the data rather than numbers, and (6) analyzing the data inductively. This result show the personal pronoun in English and Bima language there are divided forms based on singular and plural. Meanwhile English differentiated how using based on subject /object in sentence. even gender for example “he” male or”she” female. whereas In bima are not differentiated based on object or female and male but the using personal pronoun in Bima just differentiated from added clit for change form singular to plural and personal pronoun in Bima would change use based on situation, and who are talking to? That’s mean using personal pronoun in Bima were influenced by cultural system, class formal and either polite.